Omental metastases from uveal melanoma—An interesting intraoperative omental pattern appearance - Sofoklis Stavros; Athanasios Zikopoulos; Anastasios Potiris; Dimitrios Baltogiannis; Chara Skentou; Ekaterini Domali; Peter Drakakis (Clinical Case Reports)
Key Clinical Message Uveal melanomas represent approximately 5% of all human melanomas. Omental metastases are often diagnosed as secondary metastatic sites and only a few cases have been described as the first single manifestation of distant metastasis. In this case image, we illustrate the interesting appearance of the metastatic localization of metastatic uveal melanoma.